The effects of sukuk characteristics towards issuer's market valuation / Noriza Mohd Saad and Dr. Mohd Nizal Haniff - Abdol Ghapar, Dr Hjh Farha; Ismail, Mazida; Mohd Ramsi, Mohd Faizal; Md Nawi, Sofwah; Hassan, Suzana; Suhaimi, Azrina (2013)
Purpose - This main objective of the study is to investigate the impact of sukuk characteristics towards issuer's market valuation as regards to tenure, RAS rating and size of issuance in Malaysian Sukuk Market. Design/methodology/approach - Using a secondary monthly data retrieved from RAM Rating Services subscription data and Bank Negara Malaysia Info Hub website 2002:1 to 2011:12, this study develops Rating Dummies Development Based on Ordinal Method to fit with the regression model. Findings - Sukuk characteristics such RAS rating and size of issuances (tenure) have a positive (negative) effect to issuer's market valuation. Symbolize that these characteristics are important trading mechanism to enhance issuer market value. Sukuk rating is significant influenced to the issuer value such probably because it is represent the credit worthiness and indicator for default risk detection. Research limitations/implications - The scope of the study is only public listed issuer through over the counter trading in Malaysian Sukuk Market. Practical implications - Malaysian regulatory bodies like Securities Commission, RAM Rating Services, Bank Negara Malaysia and other financial institutions who are acted as banker and trustee for sukuk trading. Social implications - Sukuk issuances are syariah compliant and benefited to Muslim investor for those who are aim for life of hereafter assurance by involving interest- free based trading. Originality/value - The study provide an evidence regards to the effects of sukuk characteristics towards issuers' market value which can serve as signal to them to to make a right decision on sukuk investment to alleviate a certain default risk.